Adenoma detection with cap-assisted colonoscopy versus regular colonoscopy: a randomised controlled trial. Issue 10 (20th December 2011) - de Wijkerslooth, Thomas R; Stoop, Esther M; Bossuyt, Patrick M; Mathus-Vliegen, Elisabeth M H; Dees, Jan; Tytgat, Kristien M A J; van Leerdam, Monique E; Fockens, Paul; Kuipers, Ernst J; Dekker, Evelien
Abstract : Objective: Conventional colonoscopy (CC) is considered the reference standard for detection of colorectal neoplasia, but it can still miss a substantial number of adenomas. The use of a transparent plastic cap may improve colonic visualisation. Cap-assisted colonoscopy (CAC) was compared with CC for adenoma detection. Secondary outcomes were caecal intubation time, caecal intubation rate and the degree of discomfort of colonoscopy. Design: This is a parallel, randomised, controlled trial at two centres. Asymptomatic participants (aged 50–75 years) in a primary colonoscopy screening programme were consecutively invited. Consenting subjects were 1:1 randomised to either CAC or CC. All colonoscopies were performed by experienced endoscopists (≥1000 colonoscopies) who were trained in CAC. Colonoscopy quality indicators were prospectively recorded. Results: A total of 1380 participants were randomly allocated to CC (N=694) or CAC (N=686). Caecal intubation rate was comparable in the two groups (98% vs 99%; p=0.29). Caecal intubation time was significantly lower in the CAC group: 7.7±5.0 min with CAC vs 8.9±6.2 min with CC (p<0.001) (values mean±SD). Adenoma detection rates of all endoscopists were ≥20%. The proportion of subjects with at least one adenoma was similar in the two groups (28% vs 28%; RR 0.98; 95% CI 0.82 to 1.16), as well as the mean number of adenomas per subject (0.49±1.05 vs 0.50±1.03; p=0.91). Detection of small size, flat and proximally located adenomas was comparable. CAC participants had lower Gloucester Comfort Scores during colonoscopy (2.2±1.0 vs 2.0±1.0; p=0.03). Conclusion: CAC does not improve adenoma detection, but does reduce caecal intubation time by more than 1 min and does lessen the degree of discomfort during colonoscopy.